Liver Hemangioma Might Lead to overestimation of Liver Fibrosis by Fibroscan; A Missed Issue in Two Cases - Aalaei-Andabili, Seyed Hossein (Kowsar, 2012)
BACKGROUND: The assessment of liver fibrosis is an important way for prediction of liver disease progression and patient’s prognosis. Liver stiffness measurement (LSM) is strongly associated with stage of liver diseases. overestimation of liver fibrosis in heart failure has been reported. We would like to introduce a new leading cause of liver fibrosis overestimation by presentation of two cases. CASE PRESENTATION: one case with right lobe hemangioma has an overestimation of liver fibrosis. The result completely changed when Fibroscan was performed in patient’s left lobe. Interestingly, another case with left lobe hemangioma had overestimation of fibrosis in her left lobe but, right lob Fibroscan was normal. CONCLUSION: We found that liver hemangioma may leads to overestimation of liver stiffness and the correct inspection of liver echogenicity before any interpretation of high liver stiffness is recommended. We suggest that patient with higher level of Fibroscan score repeat it in other sides of the liver. Also, they should be evaluated by sonography for ruling out of possible confounders such as hepatic hemangioma.